Revision of the Australian species of Aphanocephalus Wollaston (Coleoptera: Discolomatidae) - Szawaryn, Karol (Zootaxa, 2025)
Australian fauna of Apahnocephalus Wollaston is not very diverse in species, however, it has a very convolute nomenclatural history. During this study an extensive material of around 750 specimens of Aphanocephalus from Australia were examined including types of all described taxa. Fifteen species of Aphanocephalus were recognized. Seven new species are described: A. calderi sp. nov., A. kukuyalanji sp. nov., A. lawrencei sp. nov., A. occidentalis sp. nov., A. queenslandicus sp. nov., A. slipinskii sp. nov., A. weiri sp. nov. Two replacement names are proposed: A. blackburni nom. nov. for A. quadrimaculatus Lea, 1921a (nec. A. quadrimaculatus Matthews, 1887) and A. leai nom. nov. for A. quadrinotatus Lea, 1921b (nec. A. quadrinotatus Grouvell, 1912). Lectotypes for A. austerus John, A. bimaculatus Grouvelle, A. bimaculatus Lea, A. hackeri John, A. nitidus Lea, A. pallidipennis Lea, A. potamophilus Lea, A. potamophilus John, A. quadrimaculatus Lea, A. quadrinotatus Lea, and Eleothreptus punctulatus Blackburn are designated to stabilize taxonomic status of these names. The following synonyms are established: A. bimaculatus Lea, 1921b and A. perlucidus John, 1941 as synonyms of A. bimaculatus Grouvelle, 1912; A potamophilus John, 1954 as a synonym of A. potamophilus Lea, 1921a; and A. poropterus Lea, 1922 as a synonym of A. pallidipennis Lea, 1921a. All herein included taxa are illustrated with colour photographs of habitus and the male and female genitalia. A key to all taxa and distribution maps are also presented. New records of feeding on various Ascomycota fungi are documented.